PEMIKIRAN AZYUMARDI AZRA TENTANG PENDIDIKAN ISLAM DI INDONESIA - Ananda, Sofi; Zailani, Zailani; Pohan, Selamat (CV. Lafadz Jaya, 2025)
This study examines Azyumardi Azra’s thoughts on Islamic education in Indonesia. Azra emphasizes the necessity of reforming Islamic education to adapt to contemporary developments while shaping human character based on Islamic values. His proposed concept aims for Islamic education to evolve in accordance with the teachings of the Qur’an and as-sunnah. The research employs a qualitative descriptive method through a literature review of Azra’s works, including books, articles, and manuscripts sourced from libraries. The findings indicate that Islamic education in Indonesia requires reform to address modern challenges. This reform involves a textual understanding of Islamic teachings and the integration of religious knowledge with general sciences. The objective is to produce a Muslim generation that is faithful, knowledgeable, and capable of adapting to changing times. Azyumardi Azra’s thoughts serve as an important inspiration for the development of Islamic education in Indonesia.